Accuracy of C-Reactive Protein Level in the Diagnosis of Acute Appendicitis on Histopathology - Asad Ullah Khan, Maaz Rehman, Muhammad Ishfaq, Habibullah Yousafzai, Kunwar Wajahat, Ahmad Arsalan Tahir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute appendicitis (AA) is one among most common condition requiring emergency surgery throughout the world. Acute appendicitis most common diagnosis in patients seeking medical help in emergency room due to acute abdomen causing 72,000 deaths among 16 million cases reported globally. This study will help the surgeons in making timely decisions, thus reducing the morbidity and mortality associated with complicated appendicitis. The aim of this study was to accuracy of C - reactive protein (CRP) levels in acute appendicitis. Material and Methods: Six-month descriptive cross-sectional research from 16 February to 16 August 2019 was completed. The Khyber Teaching Hospital in Peshawar served as the study's location. A total of 216 patients were monitored throughout this investigation. The history, clinical examination, and regular laboratory tests, such as the total leucocyte count (TLC) and differential leucocyte count (DLC) on admission, were used to make the diagnosis of acute appendicitis. All of these patients were given Nil by Mouth to prepare them for emergency surgery, and baseline testing included HBs Ag and Anti-HCV serology as well as pre-operative serum CRP levels (Liver function tests, renal function tests and serum electrolytes). Following preparation, every patient on the emergency list had surgery. Intra-operative results were recorded, and a biopsy was collected from the excised appendices and forward to histopathology for further processing. Results: The mean age in this research was 48 years, with an SD of 12.311. Male patients made up 55% of the total population, while female patients made up 45%. The diagnostic accuracy of C-reactive protein levels was determined to be 84.2% in this study. The specificity was found to be 33.3%, while the sensitivity was observed to be 85.7%. By using histopathology, it was discovered that the positive predictive value was 97.2% and the negative predictive value was 84.2%. Conclusion: According to our study, using histopathology, the diagnostic accuracy of C-reactive protein levels was 84.25% with sensitivity of 85.71%, specificity of 33.33%, and positive predictive values of 97.25% and 184.25%. The findings will also open the door for any further research in this area. . The higher CRP levels will therefore predict the complexity of acute appendicitis and help the general practitioners to do early referrals therefore avoiding life threatening complications Keywords: Acute Appendicitis, C-Reactive Protein, Histopathology, CRP, Gold Standard